1994
DOI: 10.1093/oxfordjournals.humrep.a138362
|View full text |Cite
|
Sign up to set email alerts
|

Implantation: Low implantation rate after in-vitro fertilization in patients with hydrosalpinges diagnosed by ultrasonography

Abstract: The purpose of this study was to assess whether patients with tubal infertility and a hydrosalpinx have a reduced implantation rate after in-vitro fertilization. The study included 741 patients who had 1190 consecutive oocyte aspirations. The presence or absence of hydrosalpinges was assessed by transvaginal ultrasonography on day 2 of all cycles. In 62 patients treated in 104 cycles a hydrosalpinx was diagnosed, whereas 493 patients treated in 813 cycles had no hydrosalpinx and eight patients treated in 16 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(44 citation statements)
references
References 0 publications
1
39
0
4
Order By: Relevance
“…ECF was occasionally found during IVF among patients diagnosed as hydrosalpinx (8,(14)(15)(16)(17)(18). It was thought to have negative effect on embryo implantation, the lower clinical pregnancy rate, and even lead to abortion (1,9,10).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ECF was occasionally found during IVF among patients diagnosed as hydrosalpinx (8,(14)(15)(16)(17)(18). It was thought to have negative effect on embryo implantation, the lower clinical pregnancy rate, and even lead to abortion (1,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…It was thought to have negative effect on embryo implantation, the lower clinical pregnancy rate, and even lead to abortion (1,9,10). These include embryotoxic effects of hydrosalpinx fluid, reduced endometrial receptivity (8,16) and mechanical factors or flushing effects from the reflux of hydrosalpinx fluid into the endometrial cavity to interfere the embryo implantation (14,16,17,19). However, Strandell et al (20) found that hydrosalpinx fluid did not adversely affect the normal development of human embryos and implantation, but they ignored the long-term effect of hydrosalpingeal fluid to embryos.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations